2011
DOI: 10.1021/bi2009807
|View full text |Cite
|
Sign up to set email alerts
|

Remote Exosites of the Catalytic Domain of Matrix Metalloproteinase-12 Enhance Elastin Degradation

Abstract: How does matrix metalloproteinase-12 (MMP-12 or metalloelastase) degrade elastin with high specific activity? NMR suggested soluble elastin to cover surfaces of MMP-12 far from its active site. Two of these surfaces have been found, by mutagenesis guided by the BINDSIght approach, to affect degradation and affinity for elastin substrates but not a small peptide substrate. Main exosite 1 has been extended out to Asp124 that binds calcium. Novel exosite 2 comprises residues from the II–III loop and β-strand I ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 65 publications
2
16
0
1
Order By: Relevance
“…Apart from the Hpx domains of collagenases, examples include the fibronectin type II repeats in MMP-2 and MMP-9, which contribute to the binding and degradation of elastin, gelatin, and type IV collagen (47). Recent NMR and mutagenesis studies of the Cat domain of MMP-12 characterized several exosites for elastin (48,49). Similar studies were carried out with the isolated Hpx domain of MMP-1 and a triple-helical collagen peptide (40) and suggested a role for Phe282 (Phe301 in the numbering used in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the Hpx domains of collagenases, examples include the fibronectin type II repeats in MMP-2 and MMP-9, which contribute to the binding and degradation of elastin, gelatin, and type IV collagen (47). Recent NMR and mutagenesis studies of the Cat domain of MMP-12 characterized several exosites for elastin (48,49). Similar studies were carried out with the isolated Hpx domain of MMP-1 and a triple-helical collagen peptide (40) and suggested a role for Phe282 (Phe301 in the numbering used in ref.…”
Section: Discussionmentioning
confidence: 99%
“…If not, the specific orientation of the active site to the two docking sites would likely be critical as well. Nevertheless, the principle of triangularization between exosite elastin-binding sites and the active site seem to represent a general mechanism as this was recently also shown for the elastolytic activity of MMP-12 (19).…”
Section: Discussionmentioning
confidence: 69%
“…This implies cathepsins may utilize certain surface structures in addition to the traditional substrate-binding sites in facilitating substrate binding. Recent NMR and bioinformatics studies followed by mutagenesis experiments have identified two exosites in MMP-12, which are critically contributing to elastin degradation (19,20). However, no distinct elastin-binding sites have been identified in cathepsins.…”
mentioning
confidence: 99%
“…1, A and B). Modest peak shifts also mapped to remote exosite 2 implicated in elastin digestion (42). The residue with the largest amide peak shift (⌬␦ HN Ϸ 0.22 ppm) is His-222, which coordinates the catalytic zinc and is positioned to respond to triple helix entry into the active site.…”
Section: Resultsmentioning
confidence: 99%
“…Elucidation of various encounter complexes proved crucial to capturing experimentally, for the first time to our knowledge, the productive complex with the triple helix intact, two of its chains occupying portions of the catalytic channel, and the scissile GlyϳVal peptide bond positioned correctly for catalysis. The encounter complexes form along an extended serpentine surface that centers around the II-III loop (previously designated exosite 2 of elastin interactions (42)). This might suggest a route of guided Brownian tumbling of an MMP on collagen fibrils, which could possibly hasten diffusive search to position the catalytic cleft around the triple helix.…”
mentioning
confidence: 99%